2021
DOI: 10.1016/j.dld.2021.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinations and inflammatory bowel disease – a systematic review

Abstract: Introduction: Patients with inflammatory bowel disease(IBD) are at risk of infections, many of which are preventable with vaccinations. We performed a systematic review on various aspects of vaccination in IBD. Methods: We searched PubMed, and EMBASE databases, through 31 January 2021. Primary outcomes included vaccination rates, predictors of vaccination, reasons of vaccination hesitancy and acceptance, and outcomes of intervention. Findings were presented with medians, ranges, and narrative synthesis. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…Regarding vaccinations in IBD patients, a recent systematic review has shown a low acceptance rate, ranging between 11% and 54%. 5 In the present study, we report that more than 4 in 5 (80.3%) IBD patients were ready to be vaccinated. In our study, determinants associated with COVID-19 vaccination willingness at the multivariate analysis were adherence to previous vaccinations, a perceived higher risk of COVID-19 due to IBD, male gender, degree, and alcohol intake.…”
Section: Discussionsupporting
confidence: 46%
“…Regarding vaccinations in IBD patients, a recent systematic review has shown a low acceptance rate, ranging between 11% and 54%. 5 In the present study, we report that more than 4 in 5 (80.3%) IBD patients were ready to be vaccinated. In our study, determinants associated with COVID-19 vaccination willingness at the multivariate analysis were adherence to previous vaccinations, a perceived higher risk of COVID-19 due to IBD, male gender, degree, and alcohol intake.…”
Section: Discussionsupporting
confidence: 46%
“…[34][35][36] While several international guidelines have been published, 37,38 vaccination rates in patients with IBD remain suboptimal and lower than those in the general population. In a recent systematic review, 39 the median rates of vaccination against influenza, pneumococcal pneumonia, hepatitis B, and herpes zoster were reported at 42 percent, 20 percent, 48 percent, and 11 percent, respectively. 39 The low vaccination rate could be related to patient and physician factors.…”
Section: Vaccination In Ibdmentioning
confidence: 99%
“…In a recent systematic review, 39 the median rates of vaccination against influenza, pneumococcal pneumonia, hepatitis B, and herpes zoster were reported at 42 percent, 20 percent, 48 percent, and 11 percent, respectively. 39 The low vaccination rate could be related to patient and physician factors. The reasons for vaccine hesitancy among IBD patients, defined as a delay in acceptance or refusal of vaccination despite availability of vaccination services, 40 include concern about vaccine side effects, 41 lack of awareness about the importance and safety of vaccines in immunocompromised patients, 41 and misconceptions about vaccination.…”
Section: Vaccination In Ibdmentioning
confidence: 99%
“…Vaccine hesitancy in IBD patients is not a novel concern to gastroenterologists. Prior studies have shown that IBD patients are less likely to receive vaccinations made necessary from their immunocompromised state ( 10 ). Some concerns from the past have transferred to COVID-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%